2016
DOI: 10.1111/myc.12488
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in major burns patients

Abstract: Major burn patients have characteristics that make them especially susceptible to candidemia, but few studies focused on this have been published. The objectives were to evaluate the epidemiological, microbiological and clinical aspects of candidemia in major burn patients, determining factors associated with a poorer prognosis and mortality. We conducted a retrospective observational study of candidemia between 1996 and 2012 in major burn patients admitted to the La Fe University Hospital, Valencia, Spain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…One study, however, reported a higher incidence of candidemia (11%) . With regard to the duration from ICU admission to candidemia, our findings are very close to those of Fochtmann et al (17 (9‐35) days and 16 (range 6‐89) days from admission respectively) whereas other studies reported longer median intervals of between 25 and 41 days …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One study, however, reported a higher incidence of candidemia (11%) . With regard to the duration from ICU admission to candidemia, our findings are very close to those of Fochtmann et al (17 (9‐35) days and 16 (range 6‐89) days from admission respectively) whereas other studies reported longer median intervals of between 25 and 41 days …”
Section: Discussionsupporting
confidence: 88%
“…In our study, the most commonly isolated species in blood cultures was Candida glabrata , whereas Candida albicans and Candida parapsilosis were the most common isolates from all colonisation sites. Our results reconfirm the previously reported shift in predominance from C. albicans to non‐albicans species, notably C. glabrata over the last decade or so in ICUs …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…According to recent reports, the incidence of IC has been increasing [15], but the rate has varied between different studies. In the study by Escrig et al [14], the incidence of IC was between 0 and 46.3 per 1000 admissions. Zhou et al re-ported an IC rate ranging from 6.06% to 17.54% in a single intensive care unit for burns [16].…”
Section: Discussionmentioning
confidence: 91%
“…Indwelling medical devices, such as endotracheal tubes, mechanical devices, central venous catheters, urinary catheters, and possibly parenteral nutrition, are necessary for life support in patients with major burns, but they may be sources of IC. Antibiotics are usually prescribed for prolonged prophylaxis or treatment against bacteria and represent another risk factor for IC as an opportunistic infection [14].…”
Section: Discussionmentioning
confidence: 99%